Faktor-Faktor yang Mempengaruhi Mahasiswa Perbankan Syariah IAIN Ponorogo Angkatan 2020 Tidak Menggunakan Bank Syariah Sebagai Media Utama Transaksi Keuangan - Putri, Resya Adika; Wahyuni, Ajeng (Jurnal Keuangan dan Perbankan Syariah, 2025)
Sharia banks were founded because Muslim people wanted to make transactions without fear of usury. In fact, we still find Muslim people who still use conventional banks, including Islamic banking students. This research aims to find out what factors influence Islamic Banking students at IAIN Ponorogo Class of 2020 not to use Islamic banks as the main medium for financial transactions. This research method is quantitative. Data collection techniques through questionnaires for active students majoring in Sharia Banking, Class of 2020, IAIN Ponorogo. The sampling technique used a simple random sampling technique with the Slovin formula, so a sample of 66 respondents was found. Data processing and analysis techniques use validity, reliability, classical assumption tests, multiple regression tests, and hypothesis tests using IBM SPSS 27. The results of this research are that the facility variable has a positive and significant effect with a sig value of 0.002 < 0.05, the service quality variable has a positive effect and significant with a sig value of 0.000 < 0.05, and the location variable has a positive and significant effect with a sig value of 0.003 < 0.05. Facilities, service quality and location variables simultaneously has a significant influence on the decision of IAIN Ponorogo Sharia Banking students Class of 2020 not to use sharia banks as the main medium for financial transactions with a sig value of 0.000 < 0.05.